Development and validation of a staging system for HPV-related oropharyngeal cancer by the International Collaboration on Oropharyngeal cancer Network for Staging (ICON-S): a multicentre cohort study. Issue 4 (April 2016) - O'Sullivan, Brian; Huang, Shao Hui; Su, Jie; Garden, Adam S; Sturgis, Erich M; Dahlstrom, Kristina; Lee, Nancy; Riaz, Nadeem; Pei, Xin; Koyfman, Shlomo A; Adelstein, David; Burkey, Brian B; et al.
Summary: Background: Human papillomavirus-related (HPV+) oropharyngeal cancer is a rapidly emerging disease with generally good prognosis. Many prognostic algorithms for oropharyngeal cancer incorporate HPV status as a stratification factor, rather than recognising the uniqueness of HPV+ disease. The International Collaboration on Oropharyngeal cancer Network for Staging (ICON-S) aimed to develop a TNM classification specific to HPV+ oropharyngeal cancer. Methods: The ICON-S study included patients with non-metastatic oropharyngeal cancer from seven cancer centres located across Europe and North America; one centre comprised the training cohort and six formed the validation cohorts. We ascertained patients' HPV status with p16 staining or in-situ hybridisation. We compared overall survival at 5 years between training and validation cohorts according to 7th edition TNM classifications and HPV status. We used recursive partitioning analysis (RPA) and adjusted hazard ratio (AHR) modelling methods to derive new staging classifications for HPV+ oropharyngeal cancer. Recent hypotheses concerning the effect of lower neck lymph nodes and number of lymph nodes were also investigated in an exploratory training cohort to assess relevance within the ICON-S classification. Findings: Of 1907 patients with HPV+ oropharyngeal cancer, 661 (35%) were recruited at the training centre and 1246 (65%) were enrolled at the validation centres. 5-year overall survival was similar for 7th edition TNM stage I, II, III, and IVA (respectively; 88% [95% CI 74–100]; 82% [71–95]; 84% [79–89]; and 81% [79–83]; global p=0·25) but was lower for stage IVB (60% [53–68]; p<0·0001). 5-year overall survival did not differ among N0 (80% [95% CI 73–87]), N1–N2a (87% [83–90]), and N2b (83% [80–86]) subsets, but was significantly lower for those with N3 disease (59% [51–69]; p<0·0001). Stage classifications derived by RPA and AHR models were ranked according to survival performance, and AHR-New was ranked first, followed by AHR-Orig, RPA, and 7th edition TNM. AHR-New was selected as the proposed ICON-S stage classification. Because 5-year overall survival was similar for patients classed as T4a and T4b, T4 is no longer subdivided in the re-termed ICON-S T categories. Since 5-year overall survival was similar among N1, N2a, and N2b, we re-termed the 7th edition N categories as follows: ICON-S N0, no lymph nodes; ICON-S N1, ipsilateral lymph nodes; ICON-S N2, bilateral or contralateral lymph nodes; and ICON-S N3, lymph nodes larger than 6 cm. This resembles the N classification of nasopharyngeal carcinoma but without a lower neck lymph node variable. The proposed ICON-S classification is stage I (T1–T2N0–N1), stage II (T1–T2N2 or T3N0–N2), and stage III (T4 or N3). Metastatic disease (M1) is classified as ICON-S stage IV. In an exploratory training cohort (n=702), lower lymph node neck involvement had a significant effect on survival in ICON-S stage III but had no effect in ICON-S stage I and II and was not significant as an independent factor. Overall survival was similar for patients with fewer than five lymph nodes and those with five or more lymph nodes, within all ICON-S stages. Interpretation: Our proposed ICON-S staging system for HPV+ oropharyngeal cancer is suitable for the 8th edition of the Union for International Cancer Control/American Joint Committee on Cancer TNM classification. Future work is needed to ascertain whether T and N categories should be further refined and whether non-anatomical factors might augment the full classification. Funding: None.